2016
DOI: 10.15193/zntj/2016/105/117
|View full text |Cite
|
Sign up to set email alerts
|

Content of cholesterol and fatty acid profile in sweet cream and cream made from milk produced by cows of three different breeds

Abstract: ZAWARTOŚĆ CHOLESTEROLU I PROFIL KWASÓW TŁUSZCZOWYCH W ŚMIETANCE I ŚMIETANIE Z MLEKA TRZECH RAS KRÓWS t r e s z c z e n i e Z mleka pobranego od krów trzech ras: polskiej holsztyńsko-fryzyjskiej odmiany czarno-białej, polskiej holsztyńsko-fryzyjskiej odmiany czerwono-białej i polskiej czerwonej odwirowano tłuszcz, uzyskując śmietankę, a po jej zaszczepieniu zakwasem maślarskim i inkubacji -śmietanę. W uzyskanych produktach oznaczono zawartość tłuszczu metodą butyrometryczną, cholesterolu -metodą enzymatyczną z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…These data were confirmed by Ruiz et al (2016) who found that sweetened condensed milk presented lower CLA values than raw and powdered milk. No differences were found in the profiles of fatty acids in the fats of milk, sweet cream, and cream, which confirmed their stability during the centrifugation and pasteurisation of milk as well as during the acidification with starter cultures (Bonczar et al, 2016). 7-month cheese aging showed higher CLA content than 4 months-aged cheeses, independently of the type of feeding lignosulfonate and proved that the use of diets with pelleted sunflower seeds was possible to obtain butter with a desirable nutritional value in dairy products with 23.74mg/g total lipid rumenic acid content.…”
Section: Factors Affecting Cla-content In Milk and Dairy Productsmentioning
confidence: 60%
“…These data were confirmed by Ruiz et al (2016) who found that sweetened condensed milk presented lower CLA values than raw and powdered milk. No differences were found in the profiles of fatty acids in the fats of milk, sweet cream, and cream, which confirmed their stability during the centrifugation and pasteurisation of milk as well as during the acidification with starter cultures (Bonczar et al, 2016). 7-month cheese aging showed higher CLA content than 4 months-aged cheeses, independently of the type of feeding lignosulfonate and proved that the use of diets with pelleted sunflower seeds was possible to obtain butter with a desirable nutritional value in dairy products with 23.74mg/g total lipid rumenic acid content.…”
Section: Factors Affecting Cla-content In Milk and Dairy Productsmentioning
confidence: 60%